GOOD GOVERNANCE DALAM PERSPEKTIF ETIKA BIROKRASI MENUJU TERWUJUDNYA PERILAKU APARATUR YANG BERSIH DAN BEBAS KKN - Satibi, Iwan (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2016)
This article describes the importance of implementing good governance in ethical perspectives related to apparatus behavior as part of creating a government that is clean free from corruption, collusion and nepotism. Good governance is a must that can not be bargained anymore, therefore political will from various parties, especially the government to realize the concept needs encouragement and support from all elements of the nation. In another position, the nation's deterioration caused by the "rotten" behavior of the government apparatus such as the rampant acts of corruption, collusion and nepotism (KKN), need to be addressed seriously by all parties. Therefore, various measures of anticipation and overcoming both in the perspective of the law, social structure, and morals should be carried out consistently and indiscriminately. Good governance in the administration of government will not run smoothly if the rampant cases of KKN are not dealt with professionally.